2021
DOI: 10.3389/fpsyg.2021.643653
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in Risk-Taking During the COVID-19 Pandemic: Evidence From the UK Lockdown

Abstract: In two pre-registered online studies during the COVID-19 pandemic and the early 2020 lockdown (one of which with a UK representative sample) we elicit risk-tolerance for 1,254 UK residents using four of the most widely applied risk-taking tasks in behavioral economics and psychology. Specifically, participants completed the incentive-compatible Balloon Analog Risk Task (BART) and the Binswanger-Eckel-Grossman (BEG) multiple lotteries task, as well as the Domain-Specific Risk-Taking Task (DOSPERT) and the self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 99 publications
8
33
2
Order By: Relevance
“…In the context of COVID-19, risk-compensating behaviour of mask use was not observed in a UK study based on a self-reported response to a questionnaire survey. 42 However, none of these studies were designed to elicit risk-compensating behaviour. Also, interpreting the difference between two groups of people (mask users and non-users) at around the same time as changes in behaviour pre-mask and post-mask mandate, as done in some of these studies, 40 41 43 is flawed.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of COVID-19, risk-compensating behaviour of mask use was not observed in a UK study based on a self-reported response to a questionnaire survey. 42 However, none of these studies were designed to elicit risk-compensating behaviour. Also, interpreting the difference between two groups of people (mask users and non-users) at around the same time as changes in behaviour pre-mask and post-mask mandate, as done in some of these studies, 40 41 43 is flawed.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, no evidence supporting the risk compensation argument in the context of face mask wearing is found by various studies run in different countries and different setups (Marchiori 2020 ; Bakhit et al 2021 ; Guenther et al 2021 ; Liebst et al 2021 ), with the exception of Yan et al ( 2020 ) who argue that mandatory masking caused US Americans to spend more time outside their homes. Our experiment provides the first evidence regarding the effect of mask wearing on social distancing in lines in front of stores, where there is evidence of infection (Qian et al 2021 ).…”
Section: Introductionmentioning
confidence: 93%
“…Research on the impact of major external events (crises, pandemics) on risk preferences has produced inconclusive results. With respect to Covid-19, both the general social science studies of Drichoutis and Nayga (2021) and Guenther et al (2021) , using a range of different methods, found no evidence that the pandemic had an effect on inter-temporal risk preferences. However, in terms of situational risks associated with travel and tourism during the pandemic, Luo and Lam (2020) found that risk intolerance negatively impacted on travel intention, while travel anxiety and risk intolerance moderate the indirect impacts between fear of Covid-19 and travel intentions.…”
Section: Theoretical Approachmentioning
confidence: 99%